Evaluation of efficiency of individual complex rehabilitation of patients based on the international classification of functioning - A.V. Ipatov; N.A. Sanina; I.Y. Khanyukova (Medičnì Perspektivi)
In order to determine the possibility of using a rehabilitation profile to assess the effectiveness of rehabilitation and develop a methodology for quantifying the effectiveness of rehabilitation measures in the short term in inpatients of the State Institution "Ukrainian State Research Institute of Medical and Social Disability of the Ministry of Health of Ukraine" we created a rehabilitation profile of the patient based on the principles of the International Classification of Functioning, Disability and Health (ICF). There were analyzed rehabilitation profiles of 522 patients with therapeutic pathology, musculoskeletal system diseases, and eye diseases. Rehabilitation of patients was comprehensive, with the use of methods of medical, psychological, and physical rehabilitation. The severity of dysfunctions was assessed by a quantitative scale from 0 to 4 points, where "0" – no issues, and "4" – extremely serious issue. The evaluation was performed twice by members of the multidisciplinary team: at the initial examination of the patient and at the discharge from the clinic. The statistical method and the method of expert evaluations were used to process the research results. The licensed software MS Excel for Windows was used. The study found that the proposed method of assessing the effectiveness of short-term rehabilitation is accurate and objective, it considers the initial functional status of the patient and allows to assess the quality and effectiveness of rehabilitation measures at the patient level and at the institution. Its implementation will provide a unified approach to the provision of rehabilitation services and draw conclusions about the effectiveness of rehabilitation activities of the medical institution differentially, considering the type of pathology, leading limitations of life, severity of disorders, age of patients.